2020
DOI: 10.37859/jae.v10i1.1934
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Bertahan UMKM di Tengah Pandemi Covid-19

Abstract: Dunia sedang mengalami Pandemic covid-19 termasuk Indonesia. Himbauan untuk mencegah mata rantai penyebaran virus ini mengharuskan masyarakat untuk berdiam diri dirumah. Hal ini berdampak pada ketidakstabilan ekonomi dan salah satu yang terdampak adalah UMKM. Untuk itu diperlukan strategi bertahan bagi UMKM untuk dapat terus mempertahankan bisnisnya di tengah pandemi ini. Metode penelitian yang digunakan dalam penelitian ini adalah analisis kualitatif dengan langkah eksploratif dengan teknik observasi partisip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
215

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(335 citation statements)
references
References 6 publications
(9 reference statements)
4
116
0
215
Order By: Relevance
“…The strategies for MSMEs to survive the Covid 19 pandemic according to Hardilawati (2020) include selling through e-commerce by utilizing online shopping that is popular with the government, marketing products by utilizing digital technology (digital marketing) to reach more consumers, making improvements of quality products and services, and conducting customer relationship, marketing to create consumer trust, and fostering customer loyalty. Nasution (2020) revealed that the Covid-19 pandemic has brought the market to a negative direction due to low investor sentiment.…”
Section: Previous Researchmentioning
confidence: 99%
“…The strategies for MSMEs to survive the Covid 19 pandemic according to Hardilawati (2020) include selling through e-commerce by utilizing online shopping that is popular with the government, marketing products by utilizing digital technology (digital marketing) to reach more consumers, making improvements of quality products and services, and conducting customer relationship, marketing to create consumer trust, and fostering customer loyalty. Nasution (2020) revealed that the Covid-19 pandemic has brought the market to a negative direction due to low investor sentiment.…”
Section: Previous Researchmentioning
confidence: 99%
“…(4) Doing the customer relationship marketing to earn the trust and loyalty of the costumers. (Hardilawati, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sesuai dengan web (covid19.go.id) Indonesia sudah terkonfirmasi wabah COVID-19. Dengan adanya kebijakan lockdown sangat berdampak pada UMKM (Hardilawati, 2020). Dampak COVID-19 terhadap UMKM mengalami penurunan omset yang lumayan besar karena kebijakan lockdown, karantina wilayah, berkurangnya kepercayaan masyarakat, serta sulitnya memperoleh bahan baku.…”
Section: Dampak Covid 19 Terhadap Umkm Ikhwa Comp Mojokertounclassified